THE MARKETING MIX ON PURCHASING DECISION OF MILK ULTRA HIGHT TEMPERATURE(UHT) - Asyifa Asyifa; Nurliza Nurliza; Maswadi Maswadi (Jurnal Sains Pertanian Equator, 2019)
ABSTRACTMore factors influence consumer in taking purchasing decision, that is factor product, price,distribution and promotion. The purpuse of this research is to analyze product factor (assurance,healty, high quality and flavor) price factor(price range, discount, and price according to quality), distribution factor(easy to find, proximity of location and the place) and promotion factor(frequency, information coveyor, and advertisement)of purchasing decision milk UHT on 150respondent by purposive sampling with descriptive method used analysis Structural Equation Modelling (SEM). The result show all off marketing mix (product, price, distribution and promotion) gave positive and significant influence to purchase decision of milk UH. For producers to improve products, such as using materials that are strong and durable, while for prices such as providing cheaper prices in order to compete with other dairy products, and for promotion that provides advertising products that attract and cut prices. Given that product variables, prices and promotions significantly influence the decision to purchase UHT milk. Keywords: marketing mix, purchase decision, structural equation modelling (SEM),